Panic-Buying Behavior During The Covid-19 Pandemic in Indonesia: A Social Cognitive Theoretical Model - Shine Pintor Siolemba Patiro; Hety Budiyanti; Kresno Agus Hendarto; Hendrian Hendrian (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Currently, there are limited studies on the application of the social cognitive theory in social psychology, particularly in explaining and predicting panic-buying behavior during the COVID-19 pandemic in Indonesia. This study is primarily aimed at acknowledging the role of the social cognitive theory’s development in explaining and predicting the panic-buying behavior of Indonesian citizens during the COVID-19 pandemic. The development of the theory is attained by combining emotions and subjective norms to predict the panic-buying behavior intention in Indonesia. Using a purposive sampling technique, the sample size consists of 350 respondents from various areas, such as Jakarta, Tangerang, and Banten. An online survey was performed as the data collection method. Social desirabilit response (SDR) test was also conducted by this study to guarantee the naturality of the replies from the respondents. Data were then analyzed using structural equation modeling (SEM) with a two-stage approach. The result demonstrated that emotions have the highest impact on the panic-buying behavioral intention. Further, subjective norms, self-efficacy, and social outcome expectancies have the second, third, and fourth highest impacts on panic-buying behavior, respectively. In general, the social cognitive theory model developed in this study can understand, explain, and predict panic-buying behavior during the COVID-19 pandemic outbreak in Indonesia. Overall, the results of this study may serve as basic information for practitioners and business persons by providing insights regarding the factors that form consumers’ intentions and behavior during the pandemic, relating to their buying decisions.